Ekstrak Daun Kelor (Moringa oleifera) sebagai Pengendali Infestasi Argulus sp pada Ikan Komet (Carassius auratus auratus) - E. Y, Farika; Suratma, N. A.; Damriyasa, I. M. Damriyasa (Veterinary Science and Medicine Journal, 2014)
The purpose of this study was to examine the effect of the extract of Moringa oleifera leave on Argulus sp infestation in comet fish, and determine an optimal concentration and time. Moringa oleifera leave was extracted using ethanol 96%. In total, 25 comet fishes (Carassius auratus auratus) were used in this research, in which infested by one to five individuals of Argulus sp per fish. This research used pretest and posttest design with four treatments of extract concentration of Moringa oleifera leave, namely, TI 25 mg/l, TII 37.5 mg/l, TIII 50 mg/l, TIV 62.5 mg/l, and T0 without extract as a control. Each treatment was imposed on five comet fishes. The parameter of this study was the amaount of Argulus sp released from the body of the fish. The results showed that the extract of Moringa oleifera leave had an effect on ectoparasite on comet fish. There was an indication that the more concentration of the extract of Moringa oleifera leave, the more Argulus sp released, although statistically, it was not significant (P>0.05). The optimal time of giving the extract of Moringa oleifera leave to Argulus sp infestation was 12-h.
Keywords: Comet fish; Ectoparasite Argulus sp; Moringa oleifera